Phenotypic and genetic heterogeneity of lactic acid bacteria isolated from “Alheira”, a traditional fermented sausage produced in Portugal - Albano, Helena (2010)
The aim of this study was to evaluate the phenotypic and genetic heterogeneity of lactic acid bacteria (LAB) isolated from ‘‘alheira”, a fermented sausage produced in Portugal. LAB were identified to genus and species level by phenotypic characteristics, using genus or speciesspecific primers and sequencing of the gene encoding 16S rRNA. Two-hundred and eighty-three isolates were grouped into 14 species. Lactobacillus plantarum was isolated from all sausages and Enterococcus faecalis from most of the samples. Low numbers of Lactobacillus paraplantarum, Lactobacillus brevis, Lactobacillus rhamnosus, Lactobacillus sakei, Lactobacillus zeae, Lactobacillus paracasei, Leuconostoc mesenteroides, Pediococcus pentosaceus, Pediococcus acidilactici, Weissella cibaria, Weissella viridescens and Enterococcus faecium were recorded. The genetic heterogeneity of L. plantarum and E. faecalis strains were determined by numerical analysis of DNA banding patterns obtained by RAPD–PCR. Strains of L. plantarum and E. faecalis were different from different producers. This study forms the basis from which starter cultures could be selected for production of ‘‘Alheira”.